Ignacio Álvarez-Ossorio, Siria: revolución, sectarismo y yihad, Madrid, Catarata, 2016, 190 pp. - Jaimes Ayala, Hugo Enrique (Estudios de Asia y África, 2017)
Ignacio Álvarez-Ossorio, Siria: revolución, sectarismo y yihad, Madrid, Catarata, 2016, 190 pp.